Thermoplastic elastomer and preparation method thereof

By grafting the poly(n-butyl acrylate-co-tert-butyl acrylate) copolymer in the cellulose-based thermoplastic elastomer and performing acid hydrolysis, the problem of poor elasticity of the existing cellulose-based thermoplastic elastomer is solved, and a high elasticity and high strength thermoplastic elastomer is achieved.

CN119875016AInactive Publication Date: 2025-04-25UNIV OF SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510362880.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing cellulose-based thermoplastic elastomers have poor elasticity and are difficult to meet the application needs of high elasticity and high strength.

Method used

By reacting cellulose with 2-bromoisobutyryl bromide in an ionic liquid, a cellulose initiator is obtained, and atom transfer radical polymerization is carried out under the action of a catalyst, reducing agent and ligand, poly(n-butyl acrylate-co-tert-butyl acrylate) copolymer is grafted, and finally hydrolyzed under acidic conditions to obtain cellulose grafted poly(n-butyl acrylate-co-acrylic acid) copolymer.

Benefits of technology

The obtained thermoplastic elastomer has excellent elasticity and strength properties, the elongation rate of break can reach more than 708%, the strength can exceed 10.6MPa, and the cyclic tensile performance is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875016A_ABST
    Figure CN119875016A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a thermoplastic elastomer and a preparation method thereof.The preparation method comprises the steps that cellulose is modified in an ionic liquid medium through 2-bromoisobutyryl bromide, and a cellulose initiator is obtained; the preparation method comprises the following steps: under the action of a catalyst, a reducing agent and a ligand, carrying out atom transfer radical polymerization reaction on a cellulose initiator, n-butyl acrylate and tert-butyl acrylate in a solvent A to obtain a cellulose grafted poly (n-butyl acrylate copolymerized tert-butyl acrylate) copolymer; and under the condition of a solvent B and inorganic acid, carrying out acidic hydrolysis reaction on the cellulose grafted poly (n-butyl acrylate copolymerized tert-butyl acrylate) copolymer to obtain the cellulose grafted poly (n-butyl acrylate copolymerized acrylic acid) copolymer. The thermoplastic elastomer prepared by the invention has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a thermoplastic elastomer and a preparation method thereof. Background Art

[0002] Thermoplastic elastomer (TPE) has excellent elasticity, processability, recyclability and energy-saving processability, and is an effective substitute for traditional rubber. This unique property makes TPE widely used in the automotive industry, electrical appliances, medical equipment, etc. Generally, TPE consists of a soft segment and a hard segment, which act as a soft rubber phase and a hard reinforcement phase, respectively. The former has a low glass transition temperature and acts as a matrix phase to provide elasticity and flexibility, while the latter has a high glass transition temperature, giving TPE sufficient mechanical strength to resist deformation and failure. During the polymerization process, the glass transition temperature of the copolymer can be controlled by adjusting the molar ratio of the soft segment and the hard segment, thereby improving the macroscopic mechanical behavior of the resulting thermoplastic elastomer.

[0003] In recent years, sustainable polymers have attracted considerable attention and significant development due to their excellent renewable, biodegradable and biocompatible properties. Generally, cellulose, as the most common natural polymer, has been widely studied to replace petroleum-based polymers and meet the growing market demand. Microcrystalline cellulose (MCC), which can be extracted from cellulose by hydrolysis reaction, has excellent solubility and mechanical properties due to its small particle size and high crystallinity. The Young's modulus and yield stress of MCC can reach 9GPa and 49MPa, respectively. Therefore, MCC can be widely used as a reinforcing phase in grafting polymerization and blending processes, and has great potential in a wide range of applications, including medicine, food, coatings, cosmetics, etc.

[0004] For example, the patent with the authorization number CN111187385B discloses a cellulose-based bottle brush-like thermoplastic elastomer and a preparation method thereof, wherein the specific process is to react cellulose and 2-bromoisobutyryl bromide in an ionic liquid to obtain modified cellulose. In the presence of cuprous bromide and 2,2-bipyridine, the modified cellulose is used as a macromolecular initiator to initiate an atom transfer radical polymerization reaction of butyl acrylate monomer to obtain cellulose-g-polybutyl acrylate, and in the presence of cuprous chloride and N,N,N′,N′,N″-pentamethyldiethylenetriamine, the cellulose-g-polybutyl acrylate is used as a macromolecular initiator to initiate an atom transfer radical polymerization reaction of methyl methacrylate monomer, and halogen exchange is performed during the reaction to obtain a cellulose-based bottle brush-like thermoplastic elastomer. Although the thermoplastic elastomer provided by the prior art has high mechanical properties, the elasticity of the thermoplastic elastomer is poor. Summary of the invention

[0005] The purpose of the present invention is to provide a thermoplastic elastomer and a preparation method thereof. The thermoplastic elastomer provided by the present invention has good mechanical properties.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a thermoplastic elastomer comprises the following steps: The cellulose and 2-bromoisobutyryl bromide are reacted in an ionic liquid to obtain a cellulose initiator; Under the action of a catalyst, a reducing agent and a ligand, a cellulose initiator, n-butyl acrylate and tert-butyl acrylate are subjected to an atom transfer radical polymerization reaction in a solvent A to obtain a cellulose grafted poly (n-butyl acrylate copolymerized with tert-butyl acrylate) copolymer; Under the conditions of solvent B and inorganic acid, the cellulose grafted poly (n-butyl acrylate copolymerized with tert-butyl acrylate) copolymer is subjected to an acidic hydrolysis reaction to obtain the cellulose grafted poly (n-butyl acrylate copolymerized with acrylic acid) copolymer.

[0007] As a further solution of the present invention: the mass ratio of cellulose to ionic liquid is 0.75:20; the mass ratio of cellulose to 2-bromoisobutyryl bromide is 0.75:5.32.

[0008] As a further solution of the present invention: the dissolution temperature of cellulose in the ionic liquid is 80-90° C.; the modification reaction temperature is 20-25° C., and the reaction time is 18-36 hours.

[0009] As a further solution of the present invention: the cellulose is microcrystalline cellulose; and the ionic liquid is 1-allyl-3-methylimidazolium chloride.

[0010] As a further solution of the present invention: the mass ratio of the ligand to the cellulose initiator is 2.35:16.5; the mass ratio of the catalyst to the cellulose initiator is 0.55:16.5; the mass ratio of the cellulose initiator, n-butyl acrylate and tert-butyl acrylate is 16.5:4.16-4.99:1.41-2.24.

[0011] As a further solution of the present invention: the polymerization reaction temperature is 70° C. and the time is 7 to 10 hours.

[0012] As a further solution of the present invention: the catalyst is copper bromide; the reducing agent is copper; the ligand is 2,2-bipyridine; and the solvent A is N,N-dimethylformamide.

[0013] As a further embodiment of the present invention, the volume ratio of the inorganic acid to 1,4-dioxane is 1.41-2.24:29-46.

[0014] As a further solution of the present invention: solvent B is 1,4-dioxane; the inorganic acid is concentrated hydrochloric acid with a concentration of 36%-38%; the polymerization reaction temperature is 80° C. and the reaction time is 20 hours.

[0015] A thermoplastic elastomer, the structural formula of the thermoplastic elastomer is: Among them, the mass content of cellulose initiator is 0.8% to 1.1%, the mass content of polybutyl acrylate is 63.7% to 75.3%, and the mass content of polyacrylic acid is 23.6% to 35.4%.

[0016] Beneficial effects of the present invention: 1. The present invention provides a cellulose-based bottle brush-like thermoplastic elastomer having the structural formula of the above-mentioned thermoplastic elastomer, which has cellulose as the main chain and is grafted with a copolymer (i.e., polybutyl acrylate-co-acrylic acid copolymer) side chain, so that the obtained elastomer has excellent elasticity and strength properties.

[0017] 2. The present invention provides a method for preparing the above-mentioned cellulose-based bottle brush-shaped thermoplastic elastomer, combining the biomass material cellulose with organic molecules to form a thermoplastic elastomer. First, there are a large number of hydrogen bonds within and between cellulose molecular chains, which are difficult to dissolve in organic solvents for subsequent chemical reactions. The present invention uses 2-bromoisobutyryl bromide to modify cellulose in an ionic liquid medium to promote subsequent grafting reactions. Second, gelation is prone to occur when acrylic acid is directly used for cellulose grafting reactions, and the reactivity of n-butyl acrylate and tert-butyl acrylate is similar. Therefore, the present invention uses tert-butyl acrylate, which can be hydrolyzed into acrylic acid under acidic conditions, to indirectly successfully synthesize cellulose-g-polyn-butyl acrylate-co-acrylic acid thermoplastic elastomer.

[0018] 3. The test results show that the elongation at break of the thermoplastic elastomer shown in the structural formula of the thermoplastic elastomer prepared by the present invention can reach more than 708%, the strength can reach more than 10.6MPa, the cyclic tensile performance is good, and it has excellent elasticity and strength properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 This is the H NMR spectrum of the product cellulose initiator described in Example 1 of the present invention; Figure 2This is the H NMR spectrum of the product described in Example 2 of the present invention; Figure 3 is the H NMR spectrum of the product described in Example 7 of the present invention; Figure 4 The infrared spectra of the cellulose of the present invention and the product described in Example 1; Figure 5 It is the infrared spectra of the products described in Example 2 and Example 7 of the present invention; Figure 6 The lower photo is of Example 2 of the present invention in a sticky state at room temperature; Figure 7 This is a monotonic tensile test graph of the products described in Example 7, Example 8, Example 9, Example 10 and Example 11 of the present invention; Figure 8 This is a cyclic tensile test diagram of the product obtained in Example 7 of the present invention; Fig. 9 This is a cyclic tensile test diagram of the product obtained in Example 8 of the present invention; Fig.10 This is a cyclic tensile test diagram of the product obtained in Example 9 of the present invention; Fig.11 This is a cyclic tensile test diagram of the product obtained in Example 10 of the present invention; Fig.12 This is a cyclic tensile test diagram of the product obtained in Example 11 of the present invention; Fig.13 This is an AFM height image of the product obtained in Example 7 of the present invention; Fig.14 This is an AFM height image of the product obtained in Example 8 of the present invention; Fig.15 This is an AFM height image of the product obtained in Example 9 of the present invention; Fig.16 is an AFM height image of the product obtained in Example 10 of the present invention; Fig.17 This is an AFM height image of the product obtained in Example 11 of the present invention. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0022] Example 1 Preparation of cellulose initiator Take 0.75g of dried microcrystalline cellulose and 20g of 1-allyl-3-methylimidazolium chloride, add them to a round-bottom flask, stir evenly at 80°C under vacuum, then add 7mL of N,N-dimethylformamide and stir until the cellulose is completely dissolved to obtain a uniform clear mixed solution. Move to an ice water bath, add 5.32g of 2-bromoisobutyryl bromide dropwise, and then react at room temperature for 36h. After the reaction is completed, slowly pour the reaction solution into pure water for precipitation and washing 3 times. The obtained white solid product is placed in a 50°C vacuum oven and dried for 24h to obtain a cellulose initiator.

[0023] Example 2 Preparation of Cellulose-g-Poly(n-butyl acrylate-co-tert-butyl acrylate) 1 Take 16.5 mg of cellulose initiator, dissolve it in 4 mL of N, N-dimethylformamide, then add 4.16 g of n-butyl acrylate, 2.24 g of tert-butyl acrylate, 0.55 mg of copper bromide, 2.35 mg of 2,2-bipyridine, 3 mL of N, N-dimethylformamide and 0.28 g of copper wire, and perform freeze-pump-thaw cycle degassing in liquid nitrogen for 3 times. Then react at 70 ° C for 10 hours; after the reaction is completed, the reaction solution is slowly poured into methanol for precipitation and washing 3 times, and the obtained white product is placed in a vacuum oven at 60 ° C and dried for 24 hours to obtain cellulose-g-poly (n-butyl acrylate-co-tert-butyl acrylate) 1.

[0024] Example 3 Preparation of Cellulose-g-Poly(n-butyl acrylate-co-tert-butyl acrylate)2 Take 16.5 mg of cellulose initiator, dissolve it in 4 mL of N, N-dimethylformamide, then add 4.35 g of n-butyl acrylate, 2.05 g of tert-butyl acrylate, 0.55 mg of copper bromide, 2.35 mg of 2,2-bipyridine, 3 mL of N, N-dimethylformamide and 0.28 g of copper wire, and perform three freeze-pump-thaw cycles in liquid nitrogen for degassing. Then react at 70 ° C for 10 hours. After the reaction is completed, the reaction solution is slowly poured into methanol for precipitation and washing three times. The obtained white product is placed in a vacuum oven at 60 ° C and dried for 24 hours to obtain cellulose-g-poly (n-butyl acrylate-co-tert-butyl acrylate) 2.

[0025] Example 4 Preparation of Cellulose-g-Poly(n-butyl acrylate-co-tert-butyl acrylate)3 Take 16.5 mg of cellulose initiator, dissolve it in 4 mL of N, N-dimethylformamide, then add 4.48 g of n-butyl acrylate, 1.92 g of tert-butyl acrylate, 0.55 mg of copper bromide, 2.35 mg of 2,2-bipyridine, 3 mL of N, N-dimethylformamide and 0.28 g of copper wire, and perform freeze-pump-thaw cycles for degassing in liquid nitrogen for 3 times. Then react at 70 ° C for 10 hours. After the reaction is completed, the reaction solution is slowly poured into methanol for precipitation and washing 3 times. The obtained white product is placed in a vacuum oven at 60 ° C and dried for 24 hours to obtain cellulose-g-poly (n-butyl acrylate-co-tert-butyl acrylate) 3.

[0026] Example 5 Preparation of Cellulose-g-Poly(n-butyl acrylate-co-tert-butyl acrylate)4 Take 16.5 mg of cellulose initiator, dissolve it in 4 mL of N, N-dimethylformamide, then add 4.8 g of n-butyl acrylate, 1.6 g of tert-butyl acrylate, 0.55 mg of copper bromide, 2.35 mg of 2,2-bipyridine, 3 mL of N, N-dimethylformamide and 0.28 g of copper wire, and perform three freeze-pump-thaw cycles in liquid nitrogen for degassing. Then react at 70 ° C for 10 h. After the reaction is completed, the reaction solution is slowly poured into methanol for precipitation and washing three times. The obtained white product is placed in a vacuum oven at 60 ° C and dried for 24 h to obtain cellulose-g-poly (n-butyl acrylate-co-tert-butyl acrylate) 4.

[0027] Example 6 Preparation of Cellulose-g-Poly(n-butyl acrylate-co-tert-butyl acrylate)5 Take 16.5 mg of cellulose initiator, dissolve it in 4 mL of N, N-dimethylformamide, then add 4.99 g of n-butyl acrylate, 1.41 g of tert-butyl acrylate, 0.55 mg of copper bromide, 2.35 mg of 2,2-bipyridine, 3 mL of N, N-dimethylformamide and 0.28 g of copper wire, and perform three freeze-pump-thaw cycles in liquid nitrogen for degassing. Then react at 70 ° C for 10 h. After the reaction is completed, the reaction solution is slowly poured into methanol for precipitation and washing three times. The obtained white product is placed in a vacuum oven at 60 ° C and dried for 24 h to obtain cellulose-g-poly (n-butyl acrylate-co-tert-butyl acrylate) 5.

[0028] Example 7 Preparation of Cellulose-g-Polybutyl Acrylate-co-Acrylic Acid 1 Take 1.83g of cellulose-g-poly(n-butyl acrylate-co-tert-butyl acrylate) 1, add 46mL of 1,4-dioxane and dissolve it completely in a 100mL round-bottom flask, and add 2.24mL of concentrated hydrochloric acid. Reflux and heat at 80°C for 20h. After the reaction is completed, slowly pour the reaction solution into pure water for precipitation and washing 3 times. The obtained light yellow product is placed in a vacuum oven at 60°C and dried for 24h to obtain cellulose-g-polyn-butyl acrylate-co-acrylic acid 1.

[0029] Example 8 Preparation of Cellulose-g-Polybutyl Acrylate-co-Acrylic Acid 2 Take 1.83g of cellulose-g-poly(n-butyl acrylate-co-tert-butyl acrylate) 2, add 42mL of 1,4-dioxane and dissolve it completely in a 100mL round-bottom flask, and add 2.04mL of concentrated hydrochloric acid. Reflux and heat at 80°C for 20h. After the reaction is completed, slowly pour the reaction solution into pure water for precipitation and washing 3 times. The obtained light yellow product is placed in a vacuum oven at 60°C and dried for 24h to obtain cellulose-g-polyn-butyl acrylate-co-acrylic acid 2.

[0030] Example 9 Preparation of Cellulose-g-Polybutyl Acrylate-co-Acrylic Acid 3 Take 2.06g of cellulose-g-poly(n-butyl acrylate-co-tert-butyl acrylate) 3, add 39.5mL 1,4-dioxane and dissolve completely in a 100mL round-bottom flask, add 1.92mL concentrated hydrochloric acid. Reflux and heat at 80°C for 20h. After the reaction is completed, slowly pour the reaction solution into pure water for precipitation and washing 3 times. The obtained light yellow product is placed in a vacuum oven at 60°C and dried for 24h to obtain cellulose-g-polyn-butyl acrylate-co-acrylic acid 3.

[0031] Example 10 Preparation of Cellulose-g-Polybutyl Acrylate-co-Acrylic Acid 4 Take 1.83g of cellulose-g-poly(n-butyl acrylate-co-tert-butyl acrylate) 4, add 33mL of 1,4-dioxane and dissolve it completely in a 100mL round-bottom flask, and add 1.6mL of concentrated hydrochloric acid. Reflux and heat at 80°C for 20h. After the reaction is completed, slowly pour the reaction solution into pure water for precipitation and washing 3 times. The obtained light yellow product is placed in a vacuum oven at 60°C and dried for 24h to obtain cellulose-g-polyn-butyl acrylate-co-acrylic acid 4.

[0032] Embodiment 11 Preparation of Cellulose-g-Polybutyl Acrylate-co-Acrylic Acid 5 Take 1.5g of cellulose-g-poly(n-butyl acrylate-co-tert-butyl acrylate) 5, add 29mL of 1,4-dioxane and dissolve it completely in a 100mL round-bottom flask, and add 1.41mL of concentrated hydrochloric acid. Reflux and heat at 80℃ for 20h. After the reaction, slowly pour the reaction solution into pure water for precipitation and washing 3 times. The obtained light yellow product is placed in a vacuum oven at 60℃ and dried for 24h to obtain cellulose-g-polyn-butyl acrylate-co-acrylic acid 5.

[0033] Experimental data and analysis Figure 1 This is the H NMR spectrum of the product described in Example 1. Position 1 in the figure represents the -CH 3 The chemical shift of hydrogen on the surface strongly proves the correct synthesis of the product.

[0034] Figure 2 The H NMR spectrum of the product described in Example 2, in which the chemical shifts at positions c and i correspond to poly(n-butyl acrylate)-OCH 2 The hydrogen protons in poly(tert-butyl acrylate)-C(CH 3 ) 3 The chemical shifts at d, e and f correspond to the methylene hydrogen and methyl hydrogen in poly(n-butyl acrylate), respectively. The chemical shifts at a, h and b, g correspond to the methine and methylene in the poly(n-butyl acrylate) and poly(tert-butyl acrylate) chains, respectively, which proves the successful grafting of poly(n-butyl acrylate)-co-tert-butyl acrylate side chains.

[0035] Figure 3 This is the H NMR spectrum of the product described in Example 7. In the figure, j corresponds to the hydrogen in the -COOH of polyacrylic acid. Figure 2 It can be found that the molecular chain end of polytert-butyl acrylate -OC(CH 3 ) 3 The disappearance of the peak corresponding to the upper hydrogen indicates that poly(tert-butyl acrylate) is successfully hydrolyzed into poly(acrylic acid) by acid.

[0036] Figure 4 The infrared spectra of cellulose and the product described in Example 1 are shown in FIG. 1. The infrared spectra corresponding to Example 1 in FIG. 1 show a region at 1740 cm -1 The carbonyl peak at 3496 cm -1 The intensity of the hydroxyl peak at is much reduced, which proves the successful synthesis of the cellulose initiator.

[0037] Figure 5 The infrared spectra of the products described in Example 2 and Example 7 show 1733 cm -1The absorption peak represents the carbonyl peak, 1367cm -1 The peak at corresponds to the -C(CH 3 ) 3 The CH stretching vibration of the group. In the infrared spectrum corresponding to Example 7, the -1 The broad and dispersed peaks in the range can be considered as the stretching vibrations of the carboxyl hydroxyl groups. -1 The small absorption peak at may be caused by the double frequency and combination frequency of stretching vibration and deformation vibration, which can indicate that poly(tert-butyl acrylate) is successfully hydrolyzed into poly(acrylic acid).

[0038] Figure 6 Example 2 is in a sticky state at room temperature, and cannot be tested for mechanical properties because it is sticky and soft.

[0039] Figure 7 The tensile test diagram of the products described in Examples 7, 8, 9, 10 and 11 is shown. The products described in Examples 7, 8, 9, 10 and 11 are cut into dumbbell-shaped strips with a thickness of about 0.4 mm, a width of 2 mm and a length of 35 mm for tensile testing. The results are shown in FIG. Figure 7 As shown, the fracture strength of the product obtained in Example 7 is 10.6MPa, the Young's modulus is 221MPa, and the elongation at break is 249%. The fracture strength of the product obtained in Example 8 is 5.2MPa, the Young's modulus is 173MPa, and the elongation at break is 279%. The fracture strength of the product obtained in Example 9 is 3.6MPa, the Young's modulus is 74MPa, and the elongation at break is 490%. The fracture strength of the product obtained in Example 10 is 2.8MPa, the Young's modulus is 50MPa, and the elongation at break is 610%. The fracture strength of the product obtained in Example 11 is 1.4MPa, the Young's modulus is 2MPa, and the elongation at break is 708%. This shows that the material obtained by the present invention has excellent ductility and mechanical properties.

[0040] The dumbbell-shaped specimens of Example 7 were subjected to a cyclic tensile test, and the results were as follows: Figure 8 As shown, Figure 8 This is a cyclic stretching test diagram of the product obtained in Example 7. It can be seen that in the stress-strain curve of the obtained product during the cyclic stretching process, the maximum strain values ​​of each stretching cycle are 50%, 100%, 150% and 200%, respectively.

[0041] The dumbbell-shaped specimens of Example 8 were subjected to cyclic tensile test, and the results were as follows: Fig. 9 As shown, Fig. 9The cyclic stretching test diagram of the product obtained in Example 8. It can be seen that in the stress-strain curve of the obtained product during the cyclic stretching process, the maximum strain values ​​of each stretching cycle are 50%, 100%, 150%, 200%, 250%, 300%, 350% and 400%, respectively, proving that the product has good resilience.

[0042] The dumbbell-shaped specimens of Example 9 were subjected to a cyclic tensile test, and the results were as follows: Fig.10 As shown, Fig.10 The cyclic stretching test diagram of the product obtained in Example 9. It can be seen that in the stress-strain curve of the obtained product during the cyclic stretching process, the maximum strain values ​​of each stretching cycle are 50%, 100%, 150%, 200%, 250%, 300%, 350% and 400%, respectively, proving that the product has good resilience.

[0043] The dumbbell-shaped specimens of Example 10 were subjected to a cyclic tensile test, and the results were as follows: Fig.11 As shown, Fig.11 The cyclic stretching test diagram of the product obtained in Example 10. It can be seen that in the stress-strain curve of the obtained product during the cyclic stretching process, the maximum strain values ​​of each stretching cycle are 50%, 100%, 150%, 200%, 250%, 300%, 350% and 400%, respectively, proving that the product has good resilience.

[0044] The dumbbell-shaped specimens of Example 11 were subjected to a cyclic tensile test, and the results are as follows: Fig.12 As shown, Fig.12 The cyclic stretching test diagram of the product obtained in Example 11. It can be seen that in the stress-strain curve of the obtained product during the cyclic stretching process, the maximum strain values ​​of each stretching cycle are 50%, 100%, 150%, 200%, 250%, 300%, 350% and 400%, respectively, proving that the product has good resilience.

[0045] Atomic force microscopy was performed on Example 7, and the results were as follows: Fig.13 As shown, Fig.13 This is the AFM height image of Example 7. Fig.13 Among them, Example 7 presents a uniform morphology without obvious microphase separation structure.

[0046] Atomic force microscopy was performed on Example 8, and the results were as follows: Fig.14 As shown, Fig.14 This is the AFM height image of Example 8. Fig.14 In the embodiment 8, the morphology is uniform and there is no obvious microphase separation structure.

[0047] Atomic force microscopy was performed on Example 9, and the results were as follows: Fig.15 As shown, Fig.15 This is the AFM height image of Example 9. Fig.15 In the embodiment 9, the morphology is uniform and there is no obvious microphase separation structure.

[0048] Atomic force microscopy was performed on Example 10, and the results were as follows: Fig.16 As shown, Fig.16 This is the AFM height image of Example 10. Fig.16 Among them, Example 10 presents a uniform morphology without obvious microphase separation structure.

[0049] Atomic force microscopy was performed on Example 11, and the results were as follows: Fig.17 As shown, Fig.17 This is the AFM height image of Example 11. Fig.17 Among them, Example 11 presents a uniform morphology without obvious microphase separation structure.

[0050] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a thermoplastic elastomer, characterized in that: The following steps are involved: The cellulose and 2-bromoisobutyryl bromide are reacted in an ionic liquid to obtain a cellulose initiator; Under the action of a catalyst, a reducing agent and a ligand, a cellulose initiator, n-butyl acrylate and tert-butyl acrylate are subjected to an atom transfer radical polymerization reaction in a solvent A to obtain a cellulose grafted poly (n-butyl acrylate copolymerized with tert-butyl acrylate) copolymer; Under the conditions of solvent B and inorganic acid, the cellulose grafted poly (n-butyl acrylate copolymerized with tert-butyl acrylate) copolymer is subjected to an acidic hydrolysis reaction to obtain the cellulose grafted poly (n-butyl acrylate copolymerized with acrylic acid) copolymer.

2. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: The mass ratio of cellulose to ionic liquid is 0.75:20; the mass ratio of cellulose to 2-bromoisobutyryl bromide is 0.75:5.

32.

3. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: The dissolution temperature of cellulose in the ionic liquid is 80-90°C; the modification reaction temperature is 20-25°C, and the time is 18-36h.

4. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: The cellulose is microcrystalline cellulose; and the ionic liquid is 1-allyl-3-methylimidazolium chloride.

5. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: The mass ratio of the ligand to the cellulose initiator is 2.35:16.5; the mass ratio of the catalyst to the cellulose initiator is 0.55:16.5; the mass ratio of the cellulose initiator, n-butyl acrylate and tert-butyl acrylate is 16.5:4.16-4.99:1.41-2.

24.

6. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: The polymerization reaction temperature is 70°C and the time is 7 to 10 hours.

7. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: The catalyst is copper bromide; the reducing agent is copper; the ligand is 2,2-bipyridine; and the solvent A is N,N-dimethylformamide.

8. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: The volume ratio of the inorganic acid to 1,4-dioxane is 1.41-2.24:29-46.

9. The method for preparing a thermoplastic elastomer according to claim 1, characterized in that: Solvent B is 1,4-dioxane; the inorganic acid is concentrated hydrochloric acid, and the concentration of the concentrated hydrochloric acid is 36%-38%; the polymerization reaction temperature is 80°C, and the time is 20 hours.

10. A thermoplastic elastomer, characterized in that: The thermoplastic elastomer is prepared by the method described in any one of claims 1 to 9, and the structural formula of the thermoplastic elastomer is: Among them, the mass content of cellulose initiator is 0.8% to 1.1%, the mass content of polybutyl acrylate is 63.7% to 75.3%, and the mass content of polyacrylic acid is 23.6% to 35.4%.

Citation Information

Patent Citations

  • A cellulose-based bottle brush-shaped thermoplastic elastomer and its preparation method

    CN111187385B

  • Cellulose-based bottle brush-shaped thermoplastic elastomer and preparation method thereof

    CN111187385A

  • Fluorescent thermoplastic polyacrylate elastomer with adjustable mechanical properties and preparation method thereof

    CN112094371A

  • Adhesive composition and adhesive sheet of the same, and method for producing them

    JP2001348553A